2009
DOI: 10.1093/glycob/cwp010
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of LacdiNAc-terminated glycoconjugates by mutant galactosyltransferase - A way to new glycodrugs and materials

Abstract: Human placental β1,4-galactosyltransferase-I (EC 2.4.1.38) transfers the galactosyl moiety from UDP-Gal to various GlcNAc or Glc acceptors in vivo. Here, we describe the construction of its Y284L mutant as a His 6 propeptidecatβ4GalT1 construct, in which the Gal-transferase activity was totally abolished in favor of its GalNAc-transferase activity. We used this mutant in the synthesis of three monoand bivalent LacdiNAc glycomimetics with good yields. These compounds proved to be powerful ligands of two activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
(52 reference statements)
1
29
0
Order By: Relevance
“…10 Introduction of charged groups into Nacetylhexosamine sequences increases significantly the affinity for CD69. 11 Sialylated oligosaccharides bearing negatively charged groups in Siaα2→6Gal or Siaα2→6GalNAc (SiaTn) sequences are among such high-affinity ligands for the CD69 receptor. Since these sequences form an integral part of tumor surface sialomucins, 12 they may be among the ligands initiating activation-induced apoptosis in killer lymphocytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 Introduction of charged groups into Nacetylhexosamine sequences increases significantly the affinity for CD69. 11 Sialylated oligosaccharides bearing negatively charged groups in Siaα2→6Gal or Siaα2→6GalNAc (SiaTn) sequences are among such high-affinity ligands for the CD69 receptor. Since these sequences form an integral part of tumor surface sialomucins, 12 they may be among the ligands initiating activation-induced apoptosis in killer lymphocytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…39) For example, human 1,4-galactosyltransferase was converted to 1,4-N-acetyl-galactosaminyltransferase by a single point mutation. 40) In addition, data have been obtained regarding the structure-activity relationships of sialyltransferases 41) but the roles of the amino acid residues surrounding the catalytic site have not been fully explored. In this study, we obtained information with regard to the roles of the amino acid residues located in the donor substrate-binding site of ÁNpp23ST.…”
Section: Enzyme Activities Of Mutant Enzymes Derived Frommentioning
confidence: 99%
“…[21] In both cases, the dicarboxylated disaccharide 9 and both sulfated disaccharides 12 and 13 displayed the highest effect. This correlated well with the competitive studies shown in Table 2.…”
Section: Immunoactivity Of Prepared Compoundsmentioning
confidence: 94%
“…[21] d-Mannose was used as the negative control, no inhibitory effects could be observed up to 10 mM concentrations (not shown). The results are summarized in Table 2 as Àlog IC 50 .…”
Section: Prepared Compounds As Ligands Of Nk Cell Activation Receptorsmentioning
confidence: 95%